Effectiveness of aerobic exercise and strengthening on the cardiorespiratory endurance of Paralympic basketball players - Teddy Bofosa; Betty Miangindula; Constant Nkiama (Turkish Journal of Kinesiology, 2019)
The aim of this study was to evaluate the effects of aerobic exercise and strengthening on the cardiorespiratory endurance of Paralympic basketball players. The present study was carried out within Kinshasa Martyrs Stadium in the club of Congolese association of sports for handicapped and disabled) and in three towns of Kinshasa. A total of 75 disabled persons  were randomly divided into two groups: the first group (experimental) was composed of 35 Paralympic basketball players' (beginners) with a mean age of 32.03±9.06 years and a sitting height of 43.86 ± 6.75 cm (were subjected to a three-wheel-strength wheelchair basketball and weight training program sessions of two hours a week) and the second (control) of 40 disabled persons who live in three towns of Kinshasa with a mean age of 33.2 ± 2.75 years and a sitting height of 44.07 ± 3.5 cm .The paired student parametric test t allowed us to verify the effects of physical activity on weight, waist circumference, systolic blood pressure, blood pressure diastolic, resting heart rate, forced expiratory volume and the maximum oxygen uptake after 6 months. The Paralympic basketball players' have reduced significantly their weight, waist circumference, systolic blood pressure, blood pressure diastolic, resting heart rate, respiratory rate and blood glucose than control group (p < .05). In addition they increased significantly their forced expiratory volume and maximum oxygen uptake than control group (p < .05). The regular practice of adapted physical activities allows people with physical disabilities to improve their physiological profile.